г) (x - 10)/7 = 4/3
3*(x - 10) = 4*7
3x - 30 = 28
3x = 28 + 30
3x = 58
x = 58/3 = 19 1/3
е) (2x + 0,1) - 4*(1 - 4x) = 16x - 0,4
2x + 0,1 - 4 + 16x = 16x - 0,4
2x + 16x - 16x = -0,4 - 0,1 + 4
2x = 3,5
x = 1,75
Ответ:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
г) (x - 10)/7 = 4/3
3*(x - 10) = 4*7
3x - 30 = 28
3x = 28 + 30
3x = 58
x = 58/3 = 19 1/3
е) (2x + 0,1) - 4*(1 - 4x) = 16x - 0,4
2x + 0,1 - 4 + 16x = 16x - 0,4
2x + 16x - 16x = -0,4 - 0,1 + 4
2x = 3,5
x = 1,75
Ответ:![19\frac{1}{3} 19\frac{1}{3}](https://tex.z-dn.net/?f=%2019%5Cfrac%7B1%7D%7B3%7D%20%20)
Ответ:![1,75 1,75](https://tex.z-dn.net/?f=%201%2C75%20)